2014
DOI: 10.1186/1471-2407-14-749
|View full text |Cite
|
Sign up to set email alerts
|

ERβ1: characterization, prognosis, and evaluation of treatment strategies in ERα-positive and -negative breast cancer

Abstract: BackgroundThe role and clinical value of ERβ1 expression is controversial and recent data demonstrates that many ERβ antibodies are insensitive and/or non-specific. Therefore, we sought to comprehensively characterize ERβ1 expression across all sub-types of breast cancer using a validated antibody and determine the roles of this receptor in mediating response to multiple forms of endocrine therapy both in the presence and absence of ERα expression.MethodsNuclear and cytoplasmic expression patterns of ERβ1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 73 publications
5
76
3
Order By: Relevance
“…The cancer cell line MDA-MB-231 with doxycycline-inducible ERβ expression (MDA-MB-231-ERβ) (Reese et al., 2014) was cultured in Dulbeccos Modified Eagle Medium with F12 supplement (DMEM/F12) with 10% heat-inactivated tetracycline-free fetal bovine serum (FBS) (Fisher-Scientific), 2 mM L-glutamine, 50 U/ml penicillin, 50 μg/ml streptomycin, 5 μg/ml blasticidin S (Invivogen) to select for the tetracycline repressor and 500 μg/ml zeocin (Invitrogen) to select for the ERβ expression vector. To induce ERβ expression in MDA-MB 231-ERβ cells, 15 cm 2 plates were seeded with 5 × 10 6  cells and doxycycline added at either 0.1 μg/ml (for Western blot, real-time polymerase chain reaction (qRT-PCR) and PRM) or 0.5 μg/ml (for RIME) for 24 h. The MCF-7 breast cancer cell line was cultured in Dulbecco's Modified Eagle Medium (DMEM) with 10% heat-inactivated FBS (Fisher-Scientific), 2 mM L-glutamine, 50 U/ml penicillin and 50 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The cancer cell line MDA-MB-231 with doxycycline-inducible ERβ expression (MDA-MB-231-ERβ) (Reese et al., 2014) was cultured in Dulbeccos Modified Eagle Medium with F12 supplement (DMEM/F12) with 10% heat-inactivated tetracycline-free fetal bovine serum (FBS) (Fisher-Scientific), 2 mM L-glutamine, 50 U/ml penicillin, 50 μg/ml streptomycin, 5 μg/ml blasticidin S (Invivogen) to select for the tetracycline repressor and 500 μg/ml zeocin (Invitrogen) to select for the ERβ expression vector. To induce ERβ expression in MDA-MB 231-ERβ cells, 15 cm 2 plates were seeded with 5 × 10 6  cells and doxycycline added at either 0.1 μg/ml (for Western blot, real-time polymerase chain reaction (qRT-PCR) and PRM) or 0.5 μg/ml (for RIME) for 24 h. The MCF-7 breast cancer cell line was cultured in Dulbecco's Modified Eagle Medium (DMEM) with 10% heat-inactivated FBS (Fisher-Scientific), 2 mM L-glutamine, 50 U/ml penicillin and 50 μg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…ERβ is expressed in a significant percentage of breast tumors across all subtypes [42, 43], making it a potential target in anticancer therapies. In addition, several natural and synthetic ERβ-selective agonists were well tolerated in clinical trials [44] (ClinicalTrials.gov), further elevating therapeutic feasibility of rallying ERβ antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…The most comprehensive analysis was performed on patients with breast cancer where positive expression of ERβ was associated with increased response rates to ER antagonist therapy with tamoxifen (12,22). However, the role of ER signaling in other malignancies remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggests that there is an association between the intranuclear overexpression of estrogen receptor (ER) β and higher survival rates in patients with lung (9,10), prostate (11), breast (12) and colon cancer (13). A number of studies have demonstrated that nuclear receptors are expressed in head and neck cancer (1420).…”
Section: Introductionmentioning
confidence: 99%